2021
DOI: 10.1007/s00217-021-03790-2
|View full text |Cite
|
Sign up to set email alerts
|

Ready to eat shelf-stable brown rice in pouches: effect of moisture content on product’s quality and stability

Abstract: Despite several nutritional benefits of brown rice (BR) its consumption remains limited compared to white rice. Two of the major barriers to its consumption are long cooking time and limited shelf life. However, those two hurdles can be overcome through the development of shelf-stable BR pouches to create new ready-to-eat (RTE) products, a food category that is gaining important market shares. Nevertheless, scarce information is available on the production and shelf-life stability of ready-to-eat BR products. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The L *, a *, b *, and Δ E values of KY‐38 rice were 70.36, −1.02, 8.63, and 20.6, respectively, and those parameters had significantly higher ( p < 0.05) than that of other rice samples (Table 1). Previous research findings showed that the higher the L value of rice, the lower the E value, indicating the fresher the rice (Fan et al., 2017; Federici et al., 2021; Jamila et al., 2015). Thus, in the view of the rice color parameters, the H2‐63 and H2‐73 had poor rice quality compared with other rice samples.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The L *, a *, b *, and Δ E values of KY‐38 rice were 70.36, −1.02, 8.63, and 20.6, respectively, and those parameters had significantly higher ( p < 0.05) than that of other rice samples (Table 1). Previous research findings showed that the higher the L value of rice, the lower the E value, indicating the fresher the rice (Fan et al., 2017; Federici et al., 2021; Jamila et al., 2015). Thus, in the view of the rice color parameters, the H2‐63 and H2‐73 had poor rice quality compared with other rice samples.…”
Section: Resultsmentioning
confidence: 97%
“…Water content is a crucial factor affecting rice quality and storage quality. High water content leads to grain mildew, and the higher the water content, the faster the quality decline (Federici et al., 2021). The moisture content of the rice samples varied from 12.85% to 13.56% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development of ready-to-eat brown rice products overcomes these limitations. 13 RTE fish is preserved in chilling and freezing conditions, maintaining its quality for extended periods. 14 In metros and urban areas, RTE food is a trend, catering to individuals with hectic schedules who lack the time to prepare meals.…”
Section: Ready To Eat Foodmentioning
confidence: 99%
“…In India, the majority of food is consumed at home, but food consumption outside the home has increased due to the increase in urbanization, changing lifestyle, increasing working women and less time to cook which increased the need for convenience foods [1]. The requirement for ready-to-serve/instant foods has further gained importance in the light of the COVID-19 pandemic, as they provide not only an easy solution to minimize handling and contact-free delivery of food but also are a lunch option alternative for individuals who would have normally fed at restaurants that were largely shut down during the pandemic [2].…”
Section: Introductionmentioning
confidence: 99%